Social evolution in class-structured populations - Rodrigues, A; Antonio Manuel Mendes Rodrigues (2014)
Inclusive fitness theory concerns the study of social traits. Often, individuals differ in their phenotype (e.g. size, weight, nutritional state) independently of their genetic make up, that is, individuals differ in their quality. Individuals can then be classified into different “classes” according to their quality, which enable us to understand social evolution in class-structured populations. This is important because individuals in natural populations often differ in quality, either because of intrinsic factors (e.g. size), or extrinsic factors (e.g. resource availability). My thesis concerns the evolution of social traits in class-structured populations. In chapter 1, I make a brief introduction to my thesis, providing the abstract of each chapter. In chapter 2, I outline a general theory of individual quality, where I show how individual quality impacts social evolution in two fundamental ways. In chapter 3, I show that resource heterogeneity greatly influences the evolution of conditional social behaviour. In chapter 4, I show that temporal group-size heterogeneity promotes the evolution of both conditional helping and harming. In chapter 5, I analyse the effect of individual quality on kin selection. I find that individual quality has an important impact in kin selection, which can lead to extreme forms of social behaviour. In chapter 6, I show that stable environments promote the evolution of negative density-dependent dispersal, while unstable environments promote the evolution of positive density-dependent dispersal. In chapter 7, I show that budding and low local quality promote the evolution of dispersal and cooperation.